Linguistic, Psychological, and Pedagogical Foundations in Language Skills Learning: A Literature Review - Siti Khafifah; M. Syihabuddin; Alfianor (Yayasan Pondok Pesantren Rasyidiyah Khalidiyah Amuntai, 2025)
Language learning is a multidimensional process that requires the integration of linguistic, psychological, and pedagogical foundations. This integration serves as a highly relevant conceptual framework for the development of the four Arabic language skills. This study aims to analyze and synthesize these three foundations into a coherent theoretical and practical basis for effective Arabic language teaching. The method employed is a systematic literature review (SLR). Data were collected from indexed academic databases such as Google Scholar and Garuda Portal, then classified and analyzed thematically based on three main domains: linguistics, learning psychology, and pedagogy. The analysis indicates that the linguistic foundation shapes the structural understanding (phonology, morphology, syntax) of Arabic; the psychological foundation explains internal factors such as motivation and cognition that influence language acquisition; and the pedagogical foundation translates theory into communicative and learner-centered instructional design principles. The study concludes by affirming that effective Arabic language teaching requires an integrated framework that simultaneously embraces all three of these foundations.